2019
DOI: 10.3390/sym11010068
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Superspace Approach to the Effective Action in Six-Dimensional Supersymmetric Gauge Theories

Abstract: We review the recent progress in studying the quantum structure of 6D, N = (1, 0) and N = (1, 1) supersymmetric gauge theories formulated through unconstrained harmonic superfields. The harmonic superfield approach allows one to carry out the quantization and calculations of the quantum corrections in a manifestly N = (1, 0) 1 way. The quantum effective action is constructed with the help of the background field method that secures the manifest gauge invariance of the results. Although the theories under consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The main advantage of such a formulation is the possibility to keep manifest N = (1, 0) supersymmetry at all steps of quantum calculations. In our recent papers [44][45][46][47][48][49][50] we developed the harmonic superfield approach for calculating the lowest off-shell quantum corrections in various 6D, N = (1, 0) and N = (1, 1) supersymmetric theories. In the present paper we apply this superfield technique for studying the one-loop effective action in 6D, N = (1, 0) higher-derivative gauge theory of ref.…”
Section: Jhep08(2020)169mentioning
confidence: 99%
“…The main advantage of such a formulation is the possibility to keep manifest N = (1, 0) supersymmetry at all steps of quantum calculations. In our recent papers [44][45][46][47][48][49][50] we developed the harmonic superfield approach for calculating the lowest off-shell quantum corrections in various 6D, N = (1, 0) and N = (1, 1) supersymmetric theories. In the present paper we apply this superfield technique for studying the one-loop effective action in 6D, N = (1, 0) higher-derivative gauge theory of ref.…”
Section: Jhep08(2020)169mentioning
confidence: 99%
“…In our previous works [28][29][30][31][32][33] we studied UV properties of 6D, N = (1, 0) and N = (1, 1) theories in the 6D harmonic superspace formulation. In particular, it was found that 6D, N = (1, 1) theory is off-shell finite in the one-loop approximation in the Feynman gauge, although the divergences are still present in the non-minimal gauges [33] (they vanish on shell).…”
Section: Introductionmentioning
confidence: 99%